2022
DOI: 10.1097/bpo.0000000000002145
|View full text |Cite
|
Sign up to set email alerts
|

Nonaccidental Trauma in Pediatric Elbow Fractures: When You Should Be Worried

Abstract: Background: Nonaccidental trauma (NAT) is a rising source of morbidity and mortality in the pediatric population. Fractures are often the first cause for presentation to health care providers in the case of NAT but can be misidentified as accidental. Given that elbow fractures are the most common accidental injuries among pediatric patients, they are not traditionally associated with NAT. This study aims to determine the prevalence of NAT among elbow fractures and identify common features in nonaccidental elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Nonetheless, there exist distinctive fracture characteristics that more commonly align with NAT, thereby warranting heightened vigilance from medical providers. Age is the most significant predictive factor for identifying a non-accidental source [29,57,58]. In a study by Worlock et al, approximately 10% of fractures in children under 18 months are due to abuse, compared to 0.5% of fractures in children between 19 and 60 months [57].…”
Section: Skeletal Fracturesmentioning
confidence: 99%
“…Nonetheless, there exist distinctive fracture characteristics that more commonly align with NAT, thereby warranting heightened vigilance from medical providers. Age is the most significant predictive factor for identifying a non-accidental source [29,57,58]. In a study by Worlock et al, approximately 10% of fractures in children under 18 months are due to abuse, compared to 0.5% of fractures in children between 19 and 60 months [57].…”
Section: Skeletal Fracturesmentioning
confidence: 99%
“…Tadepalli et al reviewed 4,415 elbow fractures and found that the rate of nonaccidental trauma in patients <1 year of age was 30% 4 . Another series quantified the risk that a fracture is due to nonaccidental trauma to be 13 times greater for a transphyseal fracture than for a supracondylar humeral fracture 5 .…”
Section: Traumamentioning
confidence: 99%